PENGARUH PENERAPAN ROLEPLAY UNTUK MENINGKATKAN KEMAMPUAN BICARA BAHASA INGGRIS - Arif, Muchamad (MOTORIC, 2023)
This research aims to determine the success of implementing roleplay to improve students' English speaking skills. This application has different topics at each meeting. The method used is descriptive qualitative. Observations were carried out in 3 meetings. The research subjects were 42 students, consisting of 29 female students and 13 university students. The learning media needed are YouTube and speakers. The research results show that one way to improve students' English speaking skills is by using the role play method. Role play is a dynamic and effective method for learning to speak English. This application offers various benefits, ranging from practical language application to developing soft skills such as improving communication skills, expanding vocabulary, and increasing motivation. Keywords: roleplay, skill of speaking English, youtube, motivation